Fitness of self-glazed zirconia onlays using conventional and digital impressions. (3rd April 2022) - Qian, Kun; Li, Bingqing; Pu, Tingting; Bai, Tianyi; Liu, Yihong
ABSTRACT: The fitness of self-glazed zirconia (SGZ) onlays fabricated with computer-aided design/computer-aided manufacturing was analysed, and conventional impressions (CIs) were compared with intraoral digital impressions (DIs). Onlay preparation was applied on a typodont left mandibular first molar to create 22 copy dies, which were divided into DI and CI groups. The marginal gap of DI-fabricated onlays was smaller than that of CI-fabricated onlays ( p < 0.05). In both groups, the marginal gap was larger in the distal gingival than in other regions ( p < 0.05), and a trend of decreasing marginal accuracy after thermal cycling was observed. SGZ onlays performed well for internal fitness; the overall internal gaps were 72.05 ± 8.16 and 100.96 ± 22.53 μm in Groups DI and CI, respectively. SGZ onlays exhibited clinically acceptable marginal and internal fitness values. The marginal adaptation of DI-fabricated onlays was better than that of CI-fabricated onlays.